HUBUNGAN VERBAL BULLYING DENGAN KECERDASAN INTERPERSONAL SISWA SD - Suci Perwita Sari (REKOGNISI : Jurnal Pendidikan dan Kependidikan, 2018)
This research aims to determine the magnitude of verbal bullying at SD Negeri 104206, determine the magnitude of Interpersonal Intelligence at SD Negeri 104206 and the relationship between verbal bullying and interpersonal intelligence of students at SD Negeri 104206 Sei Rotan. This research is a correlational descriptive research. This research was conducted at SD Negeri 104206 Sei Rotan for the 2017/2018 academic year with a population of 188 people and a sample of 128 people. The instrument used was a closed questionnaire for each variable with a Linkert scale. The data analysis tests used are normality, linearity, product moment correlation test and hypothesis significance test. The results of the research show that the level of verbal bullying at SD Negeri 104206 is in the sufficient category, the level of interpersonal intelligence at SD Negeri 104206 is in the sufficient category and there is a positive relationship between verbal bullying and students' interpersonal intelligence. Based on the results of the hypothesis test, it can be concluded that the higher the verbal bullying, the higher the student's interpersonal intelligence.